Stepwise surface modification of mesoporous silica and its use in poly(urethane‐urea) composite films. Issue 1 (4th September 2021) - Fakhar, Afsaneh; Sadeghi, Morteza; Dinari, Mohammad
Abstract: The compatibility between polymer matrix and filler is a vital issue in the fabrication of composites with desirable properties. To enhance the interfacial adhesion between matrix and filler, various surface modification treatments are applied. The objective of this study was to increase the affinity of silica and poly(urethane‐urea)s (PUUs), thereby improving the mechanical properties of the resulting composites. Stepwise surface modification of mesoporous silica with amine‐containing dendrimers was done. Various techniques were used to confirm the surface‐modified structure during the stepwise reaction. Additionally, the N2 adsorption–desorption method indicated a gradual reduction in surface area, pore diameter and pore volume of the particles, which warrants the gradual propagation of the dendrimers on the surface and also inside the pores. A type IV isotherm was obtained in this analysis. Two types of pre‐synthesized PUUs were chosen for composite preparation containing the surface‐modified silica with 0.5, 1, 2.5 and 5 wt% concentrations. Due to the high affinity of the dendrimers containing amine moieties on the particles with polyurethane, a proper dispersion of particles in the matrix was achieved based on scanning electron micrographs. Tensile measurements showed an increased Young's modulus and strength of polyurethane films as a result of addition of the particles. However, no significant improvement in the tensile performance of the composites was seen above 2.5 wt% particle loading due to some particle aggregations. © 2021 Society of Industrial Chemistry. Abstract : Mesoporous silica was functionalized with a dendrimer containing amine moieties using a stepwise surface modification to strengthen poly(urethane‐urea) films.